PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL BERBASIS ANIMASI POWTOON MATERI DAKWAH RASULULLAH DI MAKKAH - Nurul Fadhila; Mutiara Sari Dewi; Moh Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
PAI learning which is still shrouded in indifference, boredom, loss of focus, lack of enthusiasm, sleepiness, and even falling asleep in class is the same problem in some schools. Of course, there are various ways to deal with this. Likewise at SMAIT Ulil Albab Batam, based on a preliminary study conducted on teachers and students, researchers found the same problem and the need for learning media that was more interesting, more exciting, and not boring. Thus, the researchers developed an audio-visual learning media based on Powtoon animation. This research is a type of development research using the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. But here, the researcher only stops at the fourth stage, namely product implementation. As obtained, the average score from Media Experts is 3.7 and Material Experts is 3.5 with a maximum scale of 4, as > 3.4 belongs to the very valid category. And the results of teacher and student responses to learning products show the results of the degree of achievement of 86.82% for the group test with 10 students, 90.63% for the field test of 32 students, and 86.36% for the teacher's response to the field test. As 80-89% is classified as practical and 90-100% is classified as very practical. From this it can be seen that the media is feasible and practical in its use.